2020
DOI: 10.12659/msm.919970
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessment of Risk Factors for Renal Atrophy After Percutaneous Nephrolithotomy

Abstract: Background This study explored the risk factors for renal atrophy after percutaneous nephrolithotomy (PCNL), and provides a reference for clinical prevention of renal atrophy after PCNL. Material/Methods According to the inclusion and exclusion criteria, the clinical data of 816 patients who underwent PCNL in our hospital from May 2013 to February 2018 were retrospectively collected. Depending on whether the patient had kidney atrophy, they were divided into a renal atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This may be attributed to the association between kidney volume–related measurements and several risk factors of CKD, such as older age, elevated BP, current smoking, lower eGFR and serum albumin and higher LDL-C. Our findings are in line with those of previous studies that suggested low TKV is associated with lower eGFR [ 12 , 21 , 38 , 39 ]. Although the left kidney has a physiologically larger volume than that of the right kidney [ 51 ], a higher degree of difference may be associated with reduced kidney function due to pathologic conditions that can cause a decrease in the unilateral kidney, such as renal artery stenosis [ 52 ], urinary tract obstruction [ 53 ], kidney stones [ 54 ] or CKD [ 55 ]. As identified in our study, a greater difference in the bilateral kidneys was associated with a reduced eGFR and higher albuminuria.…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to the association between kidney volume–related measurements and several risk factors of CKD, such as older age, elevated BP, current smoking, lower eGFR and serum albumin and higher LDL-C. Our findings are in line with those of previous studies that suggested low TKV is associated with lower eGFR [ 12 , 21 , 38 , 39 ]. Although the left kidney has a physiologically larger volume than that of the right kidney [ 51 ], a higher degree of difference may be associated with reduced kidney function due to pathologic conditions that can cause a decrease in the unilateral kidney, such as renal artery stenosis [ 52 ], urinary tract obstruction [ 53 ], kidney stones [ 54 ] or CKD [ 55 ]. As identified in our study, a greater difference in the bilateral kidneys was associated with a reduced eGFR and higher albuminuria.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has found that symptomatic patients with kidney stones have an increased risk off chronic kidney disease compared with the risk of normal individuals ( Rule et al, 2009 ). A retrospective clinical study has demonstrated that 6.01% of patients with kidney stones experience renal atrophy 2 years after percutaneous nephrolithotomy; kidney stones lasting more than 12 months and multiple calyces stone are independent risk factors ( Xiangrui et al, 2020 ), indicating the serious outcomes of kidney stones. The underlying mechanisms may be associated with urinary tract obstruction, infection, and crystal-induced injury and fibrosis ( Uribarri, 2020 ).…”
Section: Discussionmentioning
confidence: 99%